Du haut de l'Olympe : perspectives américaines sur l'arme nucléaire allemande - Hébert, Philippe; Létourneau, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
Few issues have created more tensions and uneasiness in international affairs than the idea of a nuclear armed Germany. The militarist and expansionist tradition of Germany has induced in its neighbors an underlying fear of a possible revival of her past hehavior. The apparition of nuclear weapons in the international System after 1945, and the subsequent accession of Great Britain and France to the status of nuclear powers, has added a further dimension to the German problem. During the Cold War, the issue of German nuclear weapons was rarely discussed favorably, particularly in Europe. The case was different in the United States where Germany's role in the nuclear strategy of NATO was approached with a detachment seldom found in British or Trench political literature. The demise of the East-West confrontation and the unification of Germany have encouraged many American scholars, often associated with the neorealist school, to push for the end of Germany's singularisation in the nuclear field. For them, a nuclear armed Germany, if not inevitable, could well become a source of military stability in the region. Although most of them base their arguments on the merits of selective nuclear proliferation, they adopt similarly an olympian perspective towards Germany which is markedly different from what is found in European literature. Their position of course does not reflect Washington's official view on the proliferation of nuclear weapons. This paper tries to circumscribe their line of thought and argues that it closely parallels, to a certain degree, the broader American attitude towards Germany seen as an equal and reliable ally in the evolving European security context.